2008
DOI: 10.1080/14678800802539317
|View full text |Cite
|
Sign up to set email alerts
|

Decentralisation and conflict in Uganda

Abstract: Abstract:Political economists have long debated the relationship between decentralization and conflict. There has been little discussion, however, about two key aspects of decentralization: first, to which levels of local government power should be decentralized, and second, on what basis new decentralized districts should be created. In order to understand the relationship between these two aspects of decentralization and conflict I investigate here the case of Uganda, where President Yoweri Museveni and his … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 16 publications
1
55
0
Order By: Relevance
“…Hegre (2001) argue that communal conflicts are rooted in the dynamics of difference within intergroup relations where groups saw themselves as different due to the ethnic and cultural background [42]. Green (2008) found that in developing countries, such as in Uganda and Indonesia, the communal conflict that strongly associated with ethnicity [43]. Further, Van Klinklen (2007) explains that ethnic heterogeneity is the main determinants of communal conflict in decentralized Indonesia [4].…”
Section: Discussionmentioning
confidence: 99%
“…Hegre (2001) argue that communal conflicts are rooted in the dynamics of difference within intergroup relations where groups saw themselves as different due to the ethnic and cultural background [42]. Green (2008) found that in developing countries, such as in Uganda and Indonesia, the communal conflict that strongly associated with ethnicity [43]. Further, Van Klinklen (2007) explains that ethnic heterogeneity is the main determinants of communal conflict in decentralized Indonesia [4].…”
Section: Discussionmentioning
confidence: 99%
“…At sub-county level, the council operates like a parliament with elected councillors representing parishes, and technical officials responsible for health, education and development implementation. The district council is the highest local government tier and the chair the most powerful local government seat, with overall control over service delivery in the district (Green, 2008). In 2005, after 10 years of a merit-based 'no-party' system, the NRM opened up Ugandan politics to multi-party electoral competition (simultaneously extending Presidential term limits), but opposition parties have struggled to generate the necessary resources and mass popular support to compete effectively.…”
Section: Political Space For Social Accountability In Museveni's Ugandamentioning
confidence: 99%
“…The control of staff appointments by a District Services Commission whose members are selected under the influence of the district council executive has led to posts being granted along ethnic lines and has undermined accountability, as job security depends on favour rather than performance (Tripp, 2010). Incessant district creation taking the total number from 33 in 1986 to 118 in 2010 has also enabled the widespread cooptation of local elites by the NRM, while exacerbating ethnic tensions by consolidating administrations around majority ethnic groups (Green, 2008).…”
Section: Political Space For Social Accountability In Museveni's Ugandamentioning
confidence: 99%
“…Uganda has seen an explosion in the number of districts (Green, 2008) The increased number of local governments has put immense pressure on service delivery and the capacity to manage new administrations (Klaver et al 2009). This has resulted in a decline in the number of local government authorities meeting performance-assessment criteria (minimum conditions) from 80% in 200680% in to 34% in 200880% in (MoLG, 2009.…”
Section: Creation Of New Districtsmentioning
confidence: 99%